Belgrade Memorial Architecture in the „Urbanizam Beograda“ Journal 1969-1981 - Mladenović, Milja (Arhitektura i urbanizam, 2022)
The topic of the paper is the role of the urban profession in the planning of the memorial complexes and monuments in Belgrade from 1969 to 1981, during which the professional journal Urbanizam Beograda was published. Using articles published in the journal Urbanizam Beograda as its main source the paper will address the stance of the expert public in the decision-making process in the planning of memorials. This includes a review of articles on individual monuments in public spaces, urban development policies, and the most important competitions related to the memorials and monuments written about by different authors in Urbanizam Beograda. Looking at the broader historical context of Yugoslavia and its cultural policies through the prism of memorial architecture, different processes and key topics that influenced the urban design of the memorial will be addressed, as well as the regard the expert public had for the decision-making process. The research is based on an analysis of expert articles published in Urbanizam Beograda, as well as an analysis of the broader socio-political context of Belgrade, in order to expand understanding of the decisions and stance of the professional public in the period 1969 to 1981. The paper aims to establish a relationship between politics and the profession, as well as to identify the implementation of different planning mechanisms for creating collective memory, recognized in the journal Urbanizam Beograda. The results of the research point to specific articles about public spaces and competitions published in Urbanizam Beograda, in which the professional public had the autonomy to make decisions based on an interdisciplinary approach to planning, which was not always in line with the socio-political situation.